Environment Analysis of T.C Terry Tex Ltd - Mriduta, Sharma (My University, 2016)
M/S T.C. TERRY TEX LTD. is a large scale textile unit established in April 2008.The industry is engaged in manufacturing 30 TPD Terry towel and 18 TD dyed yarn. The raw material used for manufacturing is cotton with average consumption of 34.5 MTD. Number of workers working in the industry are 983 coming in four shifts i.e. A shift (7.00a.m-3.00p.m), B shift (3.00 p.m-11.00 p.m), C shift (11.00 p.m.-7.00 a.m.) and General shift (9.00a.m.-6.00p.m.).The Industry runs 24 hours a day and 358 days in a year. In the present project, environment analysis of the industry is done with reference to air, water and solid waste. The wastewater is generated mainly from dyeing unit, domestic activities, boilers and other processes like charging and backwashing of soft water system, demineralized plant etc. Hazardous solid waste is generated as ETP sludge, ash from boiler and spent oil from DG sets and non-hazardous waste like .Industry has installed 1850 KLD Effluent Treatment Plant for treatment of wastewater generated from various processes. Also, the industry has installed RO units for recycling and reuse of wastewater. Industry has installed continuous monitoring system for measurement of pH, TDS and flow at the final outlet of ETP with facility of interlocking of TDS meter with RO feed pump. The Industry has also installed continuous monitoring system for measurement of SPM from boiler stack. Industry has 30 acre plantation area in which final outlet of ETP is discharged. Industry has also installed piezometric well in plantation area to ascertain the effect of repeated application of treated wastewater on the groundwater.
M.Tech. (Environmental Science and Technology)
Keywords: Environmental; Analysis; Textile; Industry